Fixed Point for Asymptotically Non-Expansive Mappings in 2-Banach Space - Abed, Salwa S.; Ali, Rafah S. Abed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we introduced some fact in 2-Banach space. Also, we define asymptotically non-expansive mappings in the setting of 2-normed spaces analogous to asymptotically non-expansive mappings in usual normed spaces. And then prove the existence of fixed points for this type of mappings in 2-Banach spaces.